2022
DOI: 10.1038/s41598-022-13404-w
|View full text |Cite
|
Sign up to set email alerts
|

Image quality and radiation dose of dual source high pitch computed tomography in pediatric congenital heart disease

Abstract: To explore the image quality and radiation dose of dual source high-pitch cardiac computed tomography with tailored contrast injection protocols for pediatric congenital heart disease patients (CHD). In total, 27 infants with CHD (median age 109 days [IQR 6–199]) were retrospectively analyzed regarding dose length product (DLP) and effective dose (ED) after undergoing cardiothoracic CT imaging. Scan parameters were adjusted on a dual source/detector CT (DSCT) to minimize radiation dose while maintaining adequa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
(25 reference statements)
0
1
0
Order By: Relevance
“…For 70 kV, the current study showed a median E eff of 0.30 mSv with all ages up to 17 years included, and for those below 1 year of age, the median E eff was 0.22 mSv. In comparison, a recent 70 kV dual-source conventional CT study that only included young children (3.5 [0.2–6.6] months) showed a median E eff of 0.20 mSv [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…For 70 kV, the current study showed a median E eff of 0.30 mSv with all ages up to 17 years included, and for those below 1 year of age, the median E eff was 0.22 mSv. In comparison, a recent 70 kV dual-source conventional CT study that only included young children (3.5 [0.2–6.6] months) showed a median E eff of 0.20 mSv [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is mandatory to use distinctive CT protocols for pediatric examinations. The newest CT scanner generations [ 14 ] plus denoising technologies based on AI algorithms [ 15 ] are additionally of high importance.…”
Section: Introductionmentioning
confidence: 99%